Modelling The Acoustic Performance Of Inhomogeneous Micro-Perforated Panel Absorber - Mosa, Ali Ibrahim (2021)
Micro-perforated panel (MPP) absorber is increasingly gaining more popularity in noise control as a sound absorber given its facile installation, long durability, environmental friendliness and attractive appearance and as an alternative to the classical porous acoustics materials. A single MPP absorber typically features a Helmholtz resonator with a high absorption amplitude, but narrow absorption bandwidth. The main objective of this study is to obtain a wider sound absorption bandwidth by proposing an inhomogeneous perforation technique. The first step is to study the acoustic performance of a single layer MPP containing holes of two different sizes and ratios and with multiple cavity depths. Thereafter, for more improvement of the absorption bandwidth, this single MPP is cascaded with another single MPP to form a double-layer MPP model of inhomogeneous perforation. Mathematical models based on the equivalent electrical circuit method are proposed, and the absorption coefficient is calculated under a normal incidence of sound. The results show that the introduction of inhomogeneous perforation technique improves the absorption performance of the single layer MPP absorber compared to the homogenous one, especially with multi-cavity depths. The MPP layer should consist of two sets of perforation parameters set in an equal arrangement in two sub MPP areas; one of smaller perforation ratio with large hole diameter and the other of larger perforation ratio with smaller hole diameter. The proposed double layer inhomogeneous MPP model exhibits significantly wider sound absorption bandwidth and higher sound absorption amplitude than that of the conventional double-layer and even triple-layer homogeneous MPPs. The results demonstrate that the absorption bandwidth can be effectively controlled to higher frequencies region by reducing the air cavity between the two inhomogeneous MPP layers, and by decreasing the cavity depth behind the sub-MPP with small hole diameter and high perforation ratio. For the low frequency improvement, this can be achieved by increasing the cavity depth behind the sub-MPP with large hole diameter-small perforation ratio. The theoretical results were validated with the experiments by using the impedance tube method with a good agreement. This study also presents an empirical mathematical model for the single layer, multi cavity inhomogeneous MPP to conveniently obtain the required MPP parameters to have the halfabsorption bandwidth of absorption coefficient.